“Triple Helix” with the Application of High-tech in Agriculture According to Market Demand - Buong, Duong Huu (VNU Journal of Science: Policy and Management Studies, 2019)
Abstract: The policy of high-tech application in agriculture plays an important role in bringing research results into agricultural development, maximizing the release of human muscle labor, creating quality agricultural products. High, safe, meeting human needs and being competitive in the market, avoiding waste of natural resources, minimizing environmental pollution and other negative impacts on society. However, this policy still has inadequacies both in theory and practice, leading to difficulties in bringing high technology into agricultural production. This article addresses the application of the "Triple Helix" as one of the key solutions for building a high-tech agricultural model according to market demand. Keywords: High-tech Agriculture, Triple Helix, market potential, market demand. References [1] N. Sharif, Problems, Issues and Strategies for S&T Policy Analysis, Science and Public Policy 15 (4) (1988) 195-216. [2] N. Sharif, Basis for Techno-Economic Policy Analysis, Science and Public Policy, 15 (4) (1988) 217-229. [3] K Ramanathan, The Polytrophic Components of Manufacturing Technology, Technological Forecasting and Social Change, 46 (1994), 221-258. [4] ESCAP, Economic and Social Commission for Asia and the Pacific: Annual report, 21 April 1988 - 5 April 1989. [5] T. Hatzichronoglou, Revision of the High-Technology Sector and Product Classification, “OECD Science, Technology and Industry” Working Papers, 2 (1997). [6] Dương Hoa Xô, Phạm Hữu Nhượng, Phát triển nông nghiệp theo hướng công nghệ cao tại Việt Nam, Diễn đàn Khuyến nông @ Công nghệ, Đà Lạt, Lâm Đồng, 2006. [7] Etzkowitz Henry, The Triple Helix: University-Industry-Government Innovation in Action (1st Edition), ISBN-13: 978-0415964517, ISBN-10: 0415964512, 1993. [8] Trần Văn Hải, Nghiên cứu kinh nghiệm về tổ chức và hoạt động chuyển giao công nghệ của Australia, đề xuất mô hình tổ chức và hoạt động chuyển giao công nghệ phù hợp cho Việt Nam trong bối cảnh hội nhập quốc tế, Đề tài Nghị định thư, 2016. [9] Cục Ứng dụng và Phát triển công nghệ, Cung – cầu công nghệ, http://www.sati.gov.vn (Truy cập ngày 10/12/2018). [10] Chợ Công nghệ và Thiết bị Việt Nam, Trang chủ, http://www.techmartvietnam.vn (Truy cập ngày 10/12/2018). [11] Trần Văn Hải, Quy trình từ nhu cầu công nghệ đến giải mã/nghiên cứu và chuyển giao công nghệ, Hội thảo khoa học Xây dựng và phát triển sàn giao dịch thông tin, công nghệ, thiết bị tại Việt Nam, Cục Thông tin KH&CN Quốc gia, Hà Nội, 2018. [12] Karen Mundy, S. Gary Bullen, Estimating Market Potential: Is There a Market, Department of Agricultural and Applied Economics, University of Georgia, 2009. [13] Phạm Thị Sen Quỳnh, Phát triển thị trường công nghệ định hướng nhu cầu (nghiên cứu trường hợp thành phố Hải Phòng, Luận văn Thạc sĩ Quản lý KH&CN, Trường Đại học KHXH&NV, Đại học Quốc gia Hà Nội, 2016. [14] Lưu Đan Thọ, Lượng Văn Quốc, Marketing mối quan hệ và quản trị quan hệ khách hàng – Lý thuyết và tình huống thực hành ứng dụng của các công ty Việt Nam, Nhà xuất bản Tài Chính, Hà Nội, 2016. [15] Luu Tien Dung, Nguyen Thi Kim Hiep, The Revolution of agriculture 4.0 and sustainable agriculture development in Vietnam, International Conference Proceedings “Emerging issues in economics and business in the context of international integration”, Hanoi, 2017. [16] Phạm Hồng Quất, Vai trò liên kết giữa Nhà nghiên cứu – Nhà nước – Doanh nghiệp trong việc ứng dụng và thương mại hóa các kết quả nghiên cứu, Hội thảo khoa học “Tổ chức và hoạt động CGCN: Kinh nghiệm của Australia và đề xuất cho Việt Nam”, Hà Nội, 10/2015.